2001
DOI: 10.1248/bpb.24.1122
|View full text |Cite
|
Sign up to set email alerts
|

Dai-kenchu-to Enhances Accelerated Small Intestinal Movement.

Abstract: Dai-kenchu-to (Da-Jian-Zhong-Tang in Chinese) is a traditional Chinese herbal medicine, called kampo medicine in Japan, and is a mixture of dried ginger root, ginseng, zanthoxylum fruit, and malt sugar. This formula is known for its clinical effects on intestinal obstruction subsequent to laparotomy and on irritable bowel syndrome (IBS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 26 publications
2
36
1
Order By: Relevance
“…The rapid and direct action of these ingredients on intestinal epithelial cells, lymphocytes, enteric nerves, and smooth muscle cells are involved in TU‐100's vasodilatory and prokinetic effects (Satoh et al. 2001; Murata et al. 2002; Kito and Suzuki 2006; Tokita et al.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid and direct action of these ingredients on intestinal epithelial cells, lymphocytes, enteric nerves, and smooth muscle cells are involved in TU‐100's vasodilatory and prokinetic effects (Satoh et al. 2001; Murata et al. 2002; Kito and Suzuki 2006; Tokita et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous pharmacological studies have suggested that DKT and its ingredients have a wide variety of biological effects, including stimulation of gastrointestinal motility [7,10,11,[12][13][14], increases in intestinal and colonic blood flow [15][16][17], stimulation of motilin, vasoactive intestinal peptide, 5-hydroxytryptamine (serotonin), Calcitonin GeneRelated Peptide (CGRP) and substance P release [16,18-20,], contraction and relaxation of intestinal smooth muscle [21,22], improvement of postoperative bowel motility, ileus and adhesive obstruction [23][24][25][26], anti-inflammatory effects [27] and suppression of bacterial translocation possibly mediated by ginseng ingredients [28]. Thus, basic and clinical evidence-based studies are establishing support for the use of DKT worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…DKT has been shown to accelerate delayed intestinal transit induced by intestinal manipulation and/or morphine administration Fukuda et al, 2006;Tokita et al, 2007b) presumably via the stimulation of acetylcholine release and serotonin receptors, 5-HT3R and 5-HT4R (Shibata et al, 1999;Satoh et al, 2001b;Tokita et al, 2007b). On the other hand, DKT has been shown to suppress the overactivity of intestines induced by several stimuli, which may relate to its relaxing effects on the intestinal smooth muscle (Satoh et al, 2001c). Recent studies have addressed the possibility that DKT increases intestinal blood flow and ameliorates colitis via calcitonin gene-related peptide and/or adrenomedullin Kono et al, 2008).…”
Section: Introductionmentioning
confidence: 99%